Migration as a hidden risk factor in seismic fatality: a spatial modeling of the Chi-Chi earthquake and suburban syndrome - T.-H. K. Chen; T.-H. K. Chen; K.-H. E. Lin; T.-H. Lin; G.-Y. Liu; C.-H. Yeh; D. M. Ceballos (Natural Hazards and Earth System Sciences)
Suburban areas have experienced disproportionately more fatalities during major earthquakes. Place-based models attribute this spatial disparity to hazard, exposure, and social-vulnerability factors. However, the impact of migration on seismic fatality remains underexplored, primarily due to the challenges of accessing mobility data. In this study, we apply a geospatial method, the radiation model, to estimate migration patterns as a critical component of exposure and vulnerability. Analyzing the 1999 Chi-Chi earthquake in Taiwan with Poisson regression across 4052 neighborhoods, we factor in migration inflow (i.e., population traveling from other neighborhoods), income of the migrants' origin, and the indigenous-population percentage among migrants, along with other risk factors proven in previous studies. Our findings indicate that migration inflow significantly correlates with an increased number of fatalities. Furthermore, a lower income in the neighborhood of the migrants' origin is significantly associated with more fatalities at their destination. An elevated proportion of the indigenous population in the migrants' original neighborhood also significantly correlates with an increased number of fatalities, although the impact of the Chi-Chi earthquake does not predominantly affect indigenous jurisdictions. This study underscores the seismic-fatality risk on the outskirts of megacities, where migrants from lower-income and historically marginalized groups are more likely to reside for precarious employment, emphasizing the need for affordable and safe living infrastructure for the migrating population. Addressing migrants' vulnerabilities in housing will not only reduce seismic-fatality risk but also improve preparedness against other disasters and public health emergencies.